∴b-a=1,c-b=1,c-a=2,
原式=
a2+b2+c2 |
abc |
1 |
a |
1 |
b |
1 |
c |
=
a2+b2+c2 |
abc |
bc+ac+ab |
abc |
=
a2+b2+c2?bc?ac?ab |
abc |
=
a(a?c)+b(b?a)+c(c?b) |
abc |
∵b-a=1,c-b=1,c-a=2,abc=6012,
∴原式=
?2a+b+c |
6012 |
=
?2a+a+1+c |
6012 |
=
1+c?a |
6012 |
=
1+2 |
6012 |
=
1 |
2004 |
a |
bc |
b |
ca |
c |
ab |
1 |
a |
1 |
b |
1 |
c |
a2+b2+c2 |
abc |
1 |
a |
1 |
b |
1 |
c |
a2+b2+c2 |
abc |
bc+ac+ab |
abc |
a2+b2+c2?bc?ac?ab |
abc |
a(a?c)+b(b?a)+c(c?b) |
abc |
?2a+b+c |
6012 |
?2a+a+1+c |
6012 |
1+c?a |
6012 |
1+2 |
6012 |
1 |
2004 |